[The Probe Team's travel, 1994] [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1994)
A chronicle of the Probe Team's travels abroad and from Itbayat to Maguindanao.
Keywords: Probe Team -- Travel